The principle of good environmental governance in the formulation of environmental legislation in Indonesia (BIS Humanities and Social Science, 2026)
The principle of Good Environmental Governance (GEG) is defined as the application of good governance principles in the context of environmental management. These principles are important pillars in creating transparent, participatory, and accountable environmental governance. The complexity of environmental issues in various sectors involving many parties, ranging from the government, the community, to business actors, makes the application of these principles very important in the Indonesian context. Indonesian environmental legislation should not only emphasize formal rules, but also ensure that everyone is aware of and involved in environmental governance. This context is in line with the constitutional mandate as stated in Article 33 paragraph (4) and Article 28H paragraph (1) of the 1945 Constitution, as well as the provisions in Law Number 32 of 2009 concerning Environmental Protection and Management. This paper aims to analyze the application of the principle of Good Environmental Governance in the formulation of environmental legislation, identify challenges in its implementation, and formulate efforts to strengthen the principle of Good Environmental Governance in the formulation of environmental legislation in Indonesia. This research uses normative juridical research with the use of secondary data, which includes primary and secondary legal materials. The research data is analyzed inductively to answer the research questions. The results show that the principle of Good Environmental Governance has not been fully implemented in the formulation of environmental legislation in Indonesia. In reality, there are quite a number of legal and non-legal challenges that hinder the application of the principles of Good Environmental Governance in the formulation of environmental legislation. Therefore, it is necessary to strengthen the principles of Good Environmental Governance in the formulation of environmental legislation in Indonesia through the internalization of strategic environmental studies and ensuring public access at every stage of the formulation process.